(untitled) (Research, Society and Development, 2022)
This article aims to present an integrative literature review, in which it evaluates the clinical evidence of the use of collagen biostimulators for body harmonization and if there is a recommendation for the application of the product, because in the current context, biostimulators act in body rejuvenation with the purpose of harmonizing it. This is a study carried out through the MEDLINE/PubMed and ScienceDirect databases, using the following Health Science Descriptors (DeCS) in English and Portuguese: body rejuvenation, body biostimulators, dermal fillers, body contouring, calcium hydroxyapatite, poly-L-lactic acid and its combinations, refining the findings with the Boolean operator AND. A 10-year time record was taken into account with publications in the period from 2012 to 2022, clinical studies in which they had in the abstract information that covered the objective of this study. The selected studies present satisfactory results with biostimulators in off-face regions of the body, being a safe and effective practice to treat sagging and firmness of the skin, in addition to obtaining volumization and improvement in the skin’s body contours. Although studies highlight promising results in body areas, more scientific data are lacking on the use of these products in these regions.